Mechanical Injury Induces Brain Endothelial-Derived Microvesicle Release: Implications for Cerebral Vascular Injury during Traumatic Brain Injury - Andrews, Allison M.; Lutton, Evan M.; Merkel, Steven F.; Razmpour, Roshanak; Ramirez, Servio H. (Frontiers in Cellular Neuroscience, 2016)
It is well established that the endothelium responds to mechanical forces induced by changes in shear stress and mechanotransduction. However, our understanding of vascular remodeling following traumatic brain injury (TBI) remains incomplete. Recently published studies have revealed that lung and umbilical endothelial cells produce extracellular microvesicles (eMVs), such as microparticles, in response to changes in mechanical forces (blood flow and mechanical injury). Yet, to date, no studies have shown whether brain endothelial cells produce eMVs following TBI. The brain endothelium is highly specialized and forms the blood-brain barrier (BBB), which regulates diffusion and transport of solutes into the brain. This specialization is largely due to the presence of tight junction proteins (TJPs) between neighboring endothelial cells. Following TBI, a breakdown in tight junction complexes at the BBB leads to increased permeability, which greatly contributes to the secondary phase of injury. We have therefore tested the hypothesis that brain endothelium responds to mechanical injury, by producing eMVs that contain brain endothelial proteins, specifically TJPs. In our study, primary human adult brain microvascular endothelial cells (BMVEC) were subjected to rapid mechanical injury to simulate the abrupt endothelial disruption that can occur in the primary injury phase of TBI. eMVs were isolated from the media following injury at 2, 6, 24 and 48 hrs. Western blot analysis of eMVs demonstrated a time-dependent increase in TJP occludin, PECAM-1 and ICAM-1 following mechanical injury. In addition, activation of ARF6, a small GTPase linked to extracellular vesicle production, was increased after injury. To confirm these results in vivo, mice were subjected to sham surgery or TBI and blood plasma was collected 24 hrs post-injury. Isolation and analysis of eMVs from blood plasma using cryo-EM and flow cytometry revealed elevated levels of vesicles containing occludin following brain trauma. These results indicate that following TBI, the cerebral endothelium undergoes vascular remodeling through shedding of eMVs containing TJPs and endothelial markers. The detection of this shedding potentially allows for a novel methodology for real-time monitoring of cerebral vascular health (remodeling), BBB status and neuroinflammation following a TBI event.